Effects of anxiety on the visual search of elite versus sub-elite archers - Toh, Siew Fen (2016)
In competitive sports where precise aiming movement are an essential component of performance, gaze control is key to successful performances. In this study, elite and sub-elite recurve archers’ visual search behaviour during an indoor 18m archery task were investigated. Four participants were recruited and tasked to perform five ends of three arrows in two counterbalanced experimental conditions where anxiety was manipulated. Participants’ visual search behaviour was measured, where QE durations, number of fixations, absolute total fixation time, and percentage of fixation time were analysed. As predicted, there are significant differences between expertise regardless of anxiety conditions. Elite archers displayed longer QE durations (M = 725.19ms), number of fixations (M = 19.91), absolute total fixation time (M = 6303.70ms), and percentage of total fixation time (M = 76.16%) as compared to sub-elite archers (M = 251.53ms, 14.95, 2663.05ms, and 51.45% respectively). The results showed that elite demonstrated more efficient visual search behaviour compared to sub-elite archers, where longer fixations, and QE durations are often associate with better performance. By quantifying these differences, more information may be provided for practitioner to strategize and program specific training program to increase archers’ accuracy and consistency.